Tailored treatment for tuberculosis in transgender individuals: a call for a patient-centered approach from a large Italian cohort - Riccardi, Niccolò; Antonello, Roberta Maria; Ferrarese, Maurizio; Repossi, Alice; Saderi, Laura; Fumagalli, Giovanni; Besozzi, Giorgio; Sotgiu, Giovanni; Codecasa, Luigi (Monaldi archives for chest disease, 2025)
Tuberculosis (TB) diagnosis and management in special populations remain challenging. Data about TB and transgender individuals is scarce, and strategies aimed at reducing the TB burden in this at-risk group are needed. We conducted an observational monocentric study from a national reference center for TB, including transgender individuals with active TB in a low-TB burden country (Italy), over 34 years (1990-2023). Sixty-six transgender males and two transgender females (median age 30 years, interquartile range 26-38 years, 65 migrants) were included. Most patients (38/66, 57.6%) lived in poor social conditions. 65.2% (43/66) of patients were people living with HIV. Multidrug- and rifampicin-resistant tuberculosis and isoniazid-resistant TB were diagnosed in five (7.6%) and three (4.5%) patients, respectively. The overall treatment success rate was 72.7% (48/66 patients), with differences observed according to social conditions. Our study highlights the need for a tailored approach to increase treatment success in this at-risk population.